2002
DOI: 10.1016/s0735-1097(01)01738-7
|View full text |Cite
|
Sign up to set email alerts
|

A standardized definition of ischemic cardiomyopathy for use in clinical research

Abstract: Angiographically diagnosed ischemic HF is associated with shorter survival than nonischemic HF. A more extensive CAD is independently associated with shorter survival, and patients with single-vessel disease and no history of MI or revascularization should be classified as nonischemic for prognostic purposes. Standardization of the definition of ischemic cardiomyopathy will be useful in the conduct and interpretation of clinical research in HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
416
3
23

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(446 citation statements)
references
References 17 publications
4
416
3
23
Order By: Relevance
“…The presence of coronary artery disease associated to HF was assessed by standard coronary angiography according to Felker et al [14]. We considered only coronary angiography performed within one year of the CPET.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of coronary artery disease associated to HF was assessed by standard coronary angiography according to Felker et al [14]. We considered only coronary angiography performed within one year of the CPET.…”
Section: Introductionmentioning
confidence: 99%
“…Severity and size of myocardial perfusion defects, revealed at rest in anterior and inferior regions of left ventricle defined by multiple logistic regression model, were informative for the diagnosis of idiopathic dilated cardiomyopathy due to its high sensitivity and specificity. Kauno medicinos universiteto 1 Kardiologijos klinika, 2 Kardiologijos institutas, 3 Radiologijos klinika Raktažodžiai: kairiojo skilvelio sistolinė visų segmentų disfunkcija, idiopatinė dilatacinė kardiomiopatija, išeminės kilmės širdies nepakankamumas, 99m Tc-MIBI miokardo perfuzijos tyrimas, echokardiografija, koronarografija.…”
Section: Resultsunclassified
“…Noninvasive evaluation and differentiation of patients with global left ventricular systolic impairment and moderate to severe HF is difficult but very important clinical task because prognosis and treatment of patients with IDCM and IHF are different (3,4). Keeping in mind a severe overall condition of HF patients, the invasive investigations of such patients have an additional risk.…”
Section: Discussionmentioning
confidence: 99%
“…A main epicardial coronary artery was defined as the main LAD or large secondary branch, main Left Circumflex (LCx) or large secondary branch or main right coronary artery (RCA) excluding branches. This definition was based upon combined European and American guidelines, along with other respected trial data that demonstrated survival benefits in a general or heart failure population when such guideline definitions lacked clarity (5,8,12,14,24,25).…”
Section: X-ray Coronary Angiographymentioning
confidence: 99%